‘AMM DAN KHASS: PENGARUHNYA DALAM PENAFSIRAN AL-QUR’AN - Muhammad Fathoni (UIN Sayyid Ali Rahmatullah Tulungagung, 2016)
The authenticity of the Koran has been recognized by all circles of bothmuslims and non-muslims. It includes the undeniable part of the miracle of the Koran, both in terms of language and of its contents. The Koran is the most comprehensive scripture in the world which maintainde its authenticity of all forms of human intervention. It is a guidelines for everyone who wants to hold onto it in life. Therefore, the Koran covers all aspect of life that it might not present everything along with the details. Therefore, in understanding the verses of the Koran needs certain means to interpret. The use of ‘amm (general) and Khass (specific) term sare often found in the Koran. The use of these terms cover certain meaning and understanding that must be examined carefully since they bring significant effect in interpreting the verses of the Koran especially on istinbatof the lawwhich will be the basis of law and code of conduct Muslim society. Besides, the use of these terms would affect the dilalat it represents which sometimes qat’iy or dhanniy.Keywords: ‘Amm , Khass, Koran, Exegesis